Production and levels of foliar nitrogen in rocket salad fertilized with controlled-release nitrogen fertilizers and urea - Ratke,Rafael Felippe (2011)
Controlled-release nitrogen fertilizers enhance crop productivity and decrease nitrogen loss through volatilization and leaching. This study aimed at determining the effect of nitrogen treatments provided by controlled-release nitrogen fertilizers and urea. The following fertilizers were tested: 1 (agricultural urea), 2 (ammonium sulfonitrate + nitrification inhibitor, dimethylpyrazole phosphate (Entec 26®)),3 (urea + Kimberlit polymer (Kimcoat N®)) and 4 (urea + NBPT (Super N - Agrotain®)). Treatments corresponded to 0, 100, 200, 400 and 800 kg ha-1 of N with rocket salad grown inside a greenhouse, assessing the production of fresh and dry leaf mass as well as levels of foliar nitrogen. Doses of different controlled-release nitrogen fertilizers showed significant polynomial regressions for the production of rocket salad fresh leaf mass and levels of foliar nitrogen, whereby Entec 26® did not show significant polynomial regression, considering the last parameter evaluated. The production of rocket salad dry leaf mass did not display significant linear regressions. The maximal production of rocket salad fresh leaf mass was reached at doses of 600, 490, 765, and 462 kg ha-1 of N with the use of urea, Entec 26®, Kimcoat N® and Super N®, respectively.